The Role of Trust in Organizational Innovation - Katarzyna WALECKA-JANKOWSKA; Joanna ZIMMER; Anna ZGRZYWA-ZIEMAK; Ewelina PIECHOTA (Communications of International Proceedings, 2020)
Trust in organisation creates a climate conducive to information exchange, sharing ideas, and therefore innovation. It can also be a factor that will be crucial for implementing innovations. The article presents the results of the empirical research related to the determinants of innovation. The authors concentrates on one of the most important determinants, which is ‘trust’. Both practitioners and theoreticians deal with the problems of managing innovation, seeking its determinants which can emerge by minimising barriers to the creation and implementation of innovations. Trust is a decisive factor for a company’s innovativeness and performance. On the other hand, innovation can be practised as well as learned. The purpose of this article is to show how to formulate and implement corporate values to promote the development of innovations and their effective use in the development of the long-term value of an organisation. The study was conducted on 50 organisations operating in Poland were examined (they were different in terms of size, industry and ownership structure).
Keywords: Trust; Innovation; Management